Explanations: A comparison of novice and experienced teachers’ explanations in Grade 9 linear functions - Mbele, Saneliso (University of the Witwatersrand, Johannesburg, 2024)
This study examines how novice and experienced teachers explain linear functions in Grade 9 using a qualitative case study approach. Hargie’s (2006) classification of explanations into interpretive, reason-giving, and descriptive categories served as the theoretical framework. The study involved four teachers, two novice and two experienced, each delivering an introductory lesson on Grade 9 linear functions, which were video recorded for analysis. The research identified key themes in teachers' explanations: concept, structure, and procedure, which informed further subcategories. Findings reveal that teachers initially rely on their subject matter understanding when explaining concepts. Over time, experienced teachers refine their explanatory practices, enhancing learners' grasp of the concepts. This study addresses a key aspect of mathematics education by examining how novice and experienced teachers explain linear functions, a fundamental concept in the curriculum. In addition, this study makes a significant contribution to the field by offering a detailed analysis of teacher explanations, a relatively underexplored area in research. The study contributes to the broader discourse on mathematics education by highlighting the role of experience in refining teaching practices. The insights gained suggest that teacher development programs should emphasise not only content knowledge but also the evolution of effective explanatory techniques.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Explanation; novice and experienced teachers; linear functions; grade 9; SDG-4: Quality education